From America to the World: Protestant Christianity's Creation of Religious Liberty - Peter A. Lillback (Societas Dei: Jurnal Agama dan Masyarakat, 2015)
ABSTRACT: Half the population of the world to this day still has not experienced religious freedom. Religious persecution often still occurs at many places in the world. Research studies show that there is a direct correlation between religious freedom and economic prosperity. "Prosperity is the result of freedom, therefore the best way to improve the economic prosperity of a nation is to ensure freedom for its citizens." This article will first elaborate models of the relationship between church and state, and then explain the basic principle of the Bible regarding religious freedom. It further explains why incarceration of religious freedom or of conscience by the state is wrong, despite the reasons of protecting its citizens from false religion or from a cult. This paper will also explore religious persecution from the time of early church until the birth of Protestantism, and then speaks about the struggle and the protection of religious freedom. Furthermore this article goes into what underlies the constitutional protection of religious freedom in America, and then browse through the struggle and the protection of religious freedom as a struggle of the world. KEY WORDS: religious freedom, religious conflict, heresy, early church, Protestantism, religious freedom in the United States of America.